(untitled) (New York, 2005)
This book constitutes the refereed proceedings of the Second International Symposium on Stochastic Algorithms: Foundations and Applications, SAGA 2003, held in Hatfield, UK in September 2003. The 12 revised full papers presented together with three invited papers were carefully reviewed and selected for inclusion in the book. Among the topics addressed are ant colony optimization, randomized algorithms for the intersection problem, local search for constraint satisfaction problems, randomized local search and combinatorial optimization, simulated annealing, probabilistic global search, network communication complexity, open shop scheduling, aircraft routing, traffic control, randomized straight-line programs, and stochastic automata and probabilistic transformations.
Keywords: Algorithms,Stochastic approximation,Computer science,Thuật toán,Phép tính xấp xỉ,Khoa học máy tính; Congresses,Congresses,Mathematics,Congresses,Hội thảo,Hội thảo,Toán học,Hội thảo